Strategi Meningkatkan Kapasitas Penangkar Benih Padi Sawah (Oriza Sativa L) Dengan Optimalisasi Peran Kelompok Tanii - Amiruddin Saleh; Robinson Putra; Ninuk Purnaningsih (Institut Pertanian Bogor, 2016)
The role of seed farmers groups is vital in efforts to achieve food self-sufficiency. The role of seed farmers groups mainly as a production unit that provides needs of superior seed, and act as learning forum, partnership forum, and marketing units. The aim of this study was to: (1) analyze the relationship between the roles of farmer’s group and the capacity of farmer’s group for foundation seeds breeder in East Lampung District; (2) formulate strategies to increase the breeder’s capacity by a way of optimizing the roles of farmer’s group. The study was conducted in East Lampung district seed farmers group with total sample of 59 farmers, seed breeders. The method of analysis was used Pearson's correlation matrix. The results showed that: (1) in general, there were significant relationship (p≥0,05) between the roles of farmer’s group and the capacity of farmer’s group irrigated lowland rice breeder; the roles of farmer’s group that was not significantly related to innovation mastery and capacity of technology components application; the role as a production unit with the capacity of technology component application; and role of a marketing unit with the capacity of technology component application, yield orientation and forging partnership; (2) the strategy to increase the breeder’s capacity could be conducted through optimizing the role of the farmer’s group as a learning class, collaboration vessel, production unit and marketing unit.Keywords: breeder’s capacity, foundation seeds, roles of group